The Associations of Ward Head Direction and Incentive with Nurse Performance at Arun LNG Hospital, Lhokseumawe, Aceh - Irwadi Irwadi; Zulfendri Zulfendri; Destanul Aulia (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: The current transformation in the hospital care industry demands greater coordination of care across providers and across settings so as to improve quality care, improve outcomes, and reduce spending. Nurses contribute to the transformative changes by being a fully contributing member of the inter-professional team. It requires an enhanced set of knowledge, skills, attitudes, and performance among nurses around wellness and population care with a renewed focus on patient-centered care, care coordination, data analytics, and quality improvement. This study aimed to analyze the associations of ward head direction and incentive with nurse performance at Arun LNG Hospital, Lhokseumawe, Aceh.Subjects and Method: This was a cross-sectional study carried out at Arun LNG Hospital, Lhokseumawe, Aceh. A sample of 74 nurses was selected for this study by exhaustive sampling. The dependent variable was nurse performance. The independent variables were ward head direction and incentive. The data were collected by questionnaire and analyzed by a multiple logistic regression.Results: Nurse performance improved with high motivation (OR= 11.12; 95% CI= 2.66 to 46.49; p= 0.001), explicit ward head direction (OR= 4.37; 95% CI= 1.05 to 18.17; p= 0.043), and existence of incentive (OR= 5.84; 95% CI= 1.30 to 26.17; p= 0.021).Conclusion: Improved nurse performance is associated with explicit ward head direction and existence of incentive.Keywords: nurse performance, ward head direction, incentiveCorrespondence: Irwadi. Masters program in Public Health, Universitas Sumatera Utara, Medan, North Sumatera. Email: wadieadi655@gmail.com. Mobile: 08126922595.Journal of Health Policy and Management (2018), 3(2): 114-117https://doi.org/10.26911/thejhpm.2018.03.02.08